2020
DOI: 10.1002/pmrj.12432
|View full text |Cite
|
Sign up to set email alerts
|

Evaluating Correlations of Coracohumeral Ligament Thickness with Restricted Shoulder Range of Motion and Clinical Duration of Adhesive Capsulitis with Ultrasound Measurements

Abstract: Objectives The primary objective of this study is to evaluate, using ultrasound measurements, the correlation between coracohumeral ligament (CHL) thickness and restricted shoulder range of motion (ROM) in patients with adhesive capsulitis (AC). The secondary objective is to investigate the correlation between CHL thickness and disease duration. Design Prospective cross‐sectional survey. Setting Clinical research of a tertiary care hospital. Methods Overall, 65 patients with clinically diagnosed AC were enroll… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0
1

Year Published

2022
2022
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 33 publications
0
9
0
1
Order By: Relevance
“…Lu et al ( 23 ) found that US-guided distension of the shoulder joint cavity had good efficacy for the treatment of FS. However, in the frozen stage, CHL thickness correlates negatively with the Er and Ir ranges of the shoulder ( 14 ), and FS patients with thickening of the CHL do not achieve good improvement of shoulder ROM using this method alone ( 24 ). Many studies have shown that steroid drugs can effectively control pain associated with FS ( 25 ), but these drugs are relatively short acting ( 26 , 27 ).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Lu et al ( 23 ) found that US-guided distension of the shoulder joint cavity had good efficacy for the treatment of FS. However, in the frozen stage, CHL thickness correlates negatively with the Er and Ir ranges of the shoulder ( 14 ), and FS patients with thickening of the CHL do not achieve good improvement of shoulder ROM using this method alone ( 24 ). Many studies have shown that steroid drugs can effectively control pain associated with FS ( 25 ), but these drugs are relatively short acting ( 26 , 27 ).…”
Section: Discussionmentioning
confidence: 99%
“…When the CHL is thickened up to 3.0 mm, there is a high likelihood for the existence of FS. The thickening of the CHL is highly correlated with adhesions, inflammation, and stability of the shoulder joint ( 14 ). The CHL is stiffer in the frozen stage than in the freezing stage ( 24 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…But satisfaction after nonoperative treatment of first CMC osteoarthritis is not yet optimal, positive expectations of treatment outcomes are associated with higher satisfaction. Therefore, optimizing patient expectations may further improve treatment expectations and outcomes [5,6]. In another systematic review and meta-analysis which included 11 RCTs, Marotta et al compared the effectiveness of 4 different orthoses (short thermoplastic CMC splint, long thermoplastic CMC-metacarpophalangeal [MCP] splint, short neoprene CMC splint, and long neoprene CMC-MCP splint) with that of no splinting for first CMC osteoarthritis.…”
Section: Handmentioning
confidence: 99%
“…Magnetic resonance imaging (MRI) demonstrates a reduced axillary recess and thickening of the coracohumeral ligament, an important restrictor of external rotation. 1,2 Although primary adhesive capsulitis develops spontaneously, its etiology remains uncertain. Some associated factors were reported, including diabetes mellitus, thyroid diseases, breast cancer, hemiplegia, and trauma; shoulder surgery followed by immobilization can result in secondary adhesive capsulitis.…”
Section: Introductionmentioning
confidence: 99%